Water erosion of soils of agricultural lands in Belarus - Tsybulka, Mikalai M. (Journal of the Belarusian State University. Ecology, 2022)
The results of the analysis of the spread of eroded soils on agricultural lands, the quantitative assessment of factors determining the manifestation of water-erosion processes in the northern and central soil-ecological provinces of Belarus are presented. On the territory of Belarus, water erosion is caused by the runoff of meltwater and heavy rainfall, manifested on the slopes in the form of washing away the upper part of the soil cover or in the form of erosion in depth. Eroded soils are concentrated mainly on arable land. Of the total area of soils subject to water erosion, slightly washed soils predominate (57 %), medium-washed soils occupy 25 %, strongly washed soils - 4 %. Water erosion prevails in the northern and central parts of the republic, so the largest areas of washed away soils are concentrated in the Vitebsk, Mogilev and Minsk regions. Significant fluctuations in the areas of eroded soils are observed in administrative districts. The largest areas of them as part of arable land (>20 %) are in Novogrudok, Volozhinsky, Korelichsky, Goretsky and Mstislavsky districts, significant areas (15-20 %) are in the areas of the hilly-moraine landscape: Braslavsky, Gorodoksky, Lepelsky. In the northern soil-ecological province, the intensity of water-erosion processes is determined primarily by climatic conditions, secondly by geomorphological, and thirdly by soil conditions. In the central province, the soil-anthropogenic factor has a higher contribution. Therefore, in the northern province, agrotechnical techniques aimed at regulating surface runoff are a priority in choosing anti-erosion measures, in the central province - the formation of a balanced structure of crops and the introduction of soil-protective crop rotations.